HYPOLIPIDEMIC EFFECT LEUCOMISINE MODEL OF ACUTE HYPERLIPIDEMIA INDUCED BY ETHANOL - E. A. Rodnova; V. V. Ivanov; S. I. Ledyukova; V. S. Chuchalin; A. V. Ratkin; B. B. Rakhimova; I. A. Khabarov; S. M. Adekenov (Бюллетень сибирской медицины)
Leucomisine model of acute hyperlipidemia in rats induced by administration of ethanol reduces the levels of free fatty acids and triacylglycerols in serum and the content of triacylglycerols in the liver of experimental animals. Introduction sesquiterpenoid leucomisine increases the activity of enzymes antiperoxidant protecti- on – glutathione peroxidase and glutathione reductase and the level of total and reduced glutathione, which prevents the activation of lipid peroxidation in the liver caused by ethanol. Lipid-lowering effect induced by the hyperlipidemia leucomisine when, like nicotinic acid, may be due to an inhibitory effect on lipolysis in adipose tissue. Along with this leucomisine has an antioxidant effect due to the activation of enzymes antiperoxidant protect and increase the redox potential of glutathione in the liver of rats.